SWOT Analysis on The Transformation of Islamic Higher Education - Muhammad Solihin; Jalaludin Jalaludin; Mona Novita; M. Syukri Ismail (Jurnal Pendidikan Islam, 2019)
The purpose of this study was to analyze the internal and external conditions of STAI (Sekolah Tinggi Agama Islam/Islamic Higher Education) Yasni Muara Bungo in formulating a strategy for changing the form of a higher education institution using TOWS and SPACE Matrix analysis tools as new model of SWOT analysis. This is a case study using a descriptive qualitative method. Data collection techniques were conducted using interviews, surveys and questionnaires. The data obtained were analyzed using TOWS and SPACE matrices. The result of TOWS matrix analysis shows that some alternatives can be applied by STAI Yasni Muara Bungo in changing its form to IAI or Institut Agama Islam (Islamic Institute) Yasni Muara Bungo are the following: (1) Strengthening the input of higher education components (Funding / education costs); (2) Developing of educational / academic, cultural and academic ethics programs in STAI Yasni Muara Bungo; and (3) Improving the quality of the curriculum that is integrated with Islamic elements, global and modern projections. While the results of the SPACE matrix show STAI Yasni Muara Bungo is in the Aggressive quadrant, meaning that it has more dominant strengths and opportunities than weaknesses and threats, making it very possible to be developed into the Islamic Institute of Religion (IAI) Yasni Muara Bungo.